Precursor of speed traffic and increase of dimensions of rolling stock on railways of the Russia (to the 100 anniversary of the birth of Mikhail Feliksovich Verigo) - Y. M. Lazarenko (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The present article is devoted to activity of the outstanding Russian scientist, Doctor of Engineering, professor Mikhail Feliksovich Verigo, the founder of large research division - Department “Integrated tests of track and rolling stock interaction”. Scientists and specialists of department took in the past and take nowadays active part in the solution of many problems connected with ensuring scientific and technical progress on a network of the railways of Ministry of Railways of the USSR and JSC RZD. In work only two problems, in which solution the key role was played by M. F. Verigo, are noted: increase of operational speed of passenger trains to 200 km/h and increasing of carrying and available capacity due to use of increased dimensions. The results of the long-term program for the preparation of railways for the introduction of increased dimensions of cars with increased linear load were registered in the new GOST 9238 - 2013 with active assistance of JSC “Russian Railways”. According to this standard one of the larger dimensions - dimension Tpr is already widely used. In particular, the loading gondola cars are built by this GOST, as well as double-decker passenger coaches and others. Dimension Tpr, which was started to develop by M. F. Verigo, has now become a sign of a new generation of innovative rolling stock.